Using Deliberative and Qualitative Methods to Mobilize Community Around the Mental Health Needs of Rural African Americans - Ann Marie Cheney; Tiffany F. Haynes; Mary Olson; Naomi Cottoms; Keneshia Bryant; Christina M. Reaves; Michael R. Reich; Geoffrey M. Curran; Greer Sullivan (Taylor & Francis Group, 2018)
Abstract-Deliberative methods obtain informed and well-reasoned public input on health topics but are rarely accompanied by rigorous qualitative methods that can ground findings in community members' shared experiences. In this project, we used Deliberative Democracy Forums, a deliberative process, to bring diverse community members together to collectively discuss mental health among rural African Americans, brainstorm solutions to address mental health needs, deliberate alternate solutions, and indicate steps for future action. By using rigorous qualitative methods to document the deliberative process and analyze deliberative dialogue, we produced a strong evidence base to inform future health care policy and research. In this article, we document our approach, present forum findings, and discuss the impact of deliberation on policy and research. We conclude that the combination of deliberative process and qualitative methods used in our project can produce a deeply contextualized understanding of mental health and identify community-initiated solutions to address mental health needs in resource-poor communities, which can help guide public health research and provide an evidence base for public health policy.